Peningkatan Perilaku Hidup Bersih dan Sehat Melalui Edukasi Sikat Gigi di SDN Kawengan - Kharisma Nur Sabila Arsilia; Lutfia Ardiyanti; Ahmad Dini Fajar Durori; M. Agus Afifudin; Rafif Eka Harya Dzaki; Erick Kurniawan; Dayyan Tsabitul Azmi; Herianto (Kreativasi : Journal of Community Empowerment, 2023)
At SDN Kawengan, Kedewan District, Bojonegoro Regency, in August 2023 a socialization event was held. The aim of this socialization is to teach Kawengan Elementary School students how to brush their teeth properly and correctly as a form of concern for the health of their teeth and mouth. It will also teach children how important it is to keep their teeth and mouth healthy to avoid diseases such as cavities, gingivitis, gum infections, canker sores, and broken teeth. To maintain oral and dental health, you must brush your teeth twice a day, before bed and after breakfast. and you have to brush your teeth for 2 minutes longer to remove dirt stuck to your teeth, using a toothbrush with soft bristles and using the right toothpaste. Lectures, questions and answers, and direct practice are socialization techniques used in socialization. The results show that children better understand how to keep their teeth and mouth healthy and better understand the importance of caring for and maintaining their health.